The Relationship of Tea Consumption Habits with Incidences of Anemia in Adolescent Girls at Pekanbaru City - Paramita, Irma Susan; Atasasih, Hesti; Mulyani, Sri; Fitri, Fitri; Afifah, Raidah (Jurnal Kesehatan Komunitas, 2024)
Anemia is a condition where there is a lack of red blood cells below normal, one of which is caused by consuming iron inhibitors such as tannins in tea. Tannins are known to inhibit the absorption of iron, especially the heme non-iron category. Drinking tea at the same time as eating can inhibit the absorption of Fe and thus affect hemoglobin levels. This study aims to determine the relationship between tea consumption habits and the incidence of anemia in young women at MTsN 3 Pekanbaru. This type of research is descriptive with a cross sectional design. The research sample of 64 female adolescent respondents was obtained using purposive sampling. Sampling used inclusion and exclusion criteria. Data on tea consumption habits was obtained using the SQ-FFQ (Semi-Quantitative Food Frequency) method and using a questionnaire. Hemoglobin level data was obtained by taking blood using the Diaspect device. The results of the study showed that 68,8% of respondents drank tea at the same time as eating, the percentage of respondents who consumed tea in the occasional category if the score was ≥ 10-14,9 with a frequency of 1-2x/week was 53,1% and the percentage of respondents who have a hemoglobin level of ≥12 g/dl with a category of no iron deficiency anemia of 65,5%.The conclusion of this studyis that there is no significant relationship between the habit of drinking tea and the incidence of anemia but there is a significant relationship between the time of tea consumption and the incidence of anemia in Adolescent girls. Keywords : Tea Consumption, Anemia incidence, Adolescent girls.